2006
DOI: 10.1177/0013916505280083
|View full text |Cite
|
Sign up to set email alerts
|

Children's Liking of Landscape Paintings as a Function of Their Perceptions of Prospect, Refuge, and Hazard

Abstract: Prospect-refuge theory was used to study children's aesthetic responses to landscape paintings. Sixty-seven children between the ages of 8 and 15 years reported their liking for 28 landscape paintings and their perceptions of the degree of prospect, refuge, and hazard in those paintings. Consistent with expectations, children were able to express systematic preferences and judgments of degrees of prospect, refuge, and hazard. Liking was significantly related to perceptions of prospect, to interactions between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…This theory would explain our preference for panoramas and elevations, which at the same time provide control and protection allowing a broad view. A study conducted on a sample of children tested this hypothesis, resulting in only a partial confirmation, as the prospect factor was found to be closely related to aesthetic preference whereas the refuge factor did not have the same statistical significance (Fisher & Shrout, 2006). Both theories follow the general idea that Wilson (1984) called biophilia, a supposed innate bond between human beings and the other living creatures developed in the phylogenesis as functional to the survival of the species.…”
Section: Place As a Stimulusmentioning
confidence: 99%
“…This theory would explain our preference for panoramas and elevations, which at the same time provide control and protection allowing a broad view. A study conducted on a sample of children tested this hypothesis, resulting in only a partial confirmation, as the prospect factor was found to be closely related to aesthetic preference whereas the refuge factor did not have the same statistical significance (Fisher & Shrout, 2006). Both theories follow the general idea that Wilson (1984) called biophilia, a supposed innate bond between human beings and the other living creatures developed in the phylogenesis as functional to the survival of the species.…”
Section: Place As a Stimulusmentioning
confidence: 99%
“…All the other age groups (ninth graders, college students, and older adults) did not display a preference for the savanna and preferred the other biomes instead (Fisher & Shrout, 2006). This study demonstrates how with age, this innate preference for areas high in prospect and refuge, like the savanna, can be modified by experience and familiarity (Kaplan, 1987).…”
Section: Previous Workmentioning
confidence: 71%
“…In their widely cited article Balling and Falk (1982) compared children's preferences to visit scenes in photographs of biomes: deciduous forest, coniferous forest, tropical rain forest, desert, and the savanna (Fisher & Shrout, 2006). Savannas are considered environments with both prospect and refuge elements.…”
Section: Previous Workmentioning
confidence: 99%
“…Appleton (1988) suggested that our evolution has likely endowed us with powerful and immediate reactions to environments, as this directly affects our likelihood of survival. However, research in this area is limited (Fischer & Shrout, 2006;Klopp & Mealey, 1998;Mealey & Theis, 1995;Stamps, 2008).…”
Section: Habitat Selection Theorymentioning
confidence: 99%